Pengaruh Kompetensi SDM, Pengendalian Internal, dan Teknologi Informasi terhadap Efektivitas Kerja Pegawai BPKAD Batam - Ramadhona Ramadhona; Sumardin Sumardin; Sabri Sabri (Asosiasi Ide Bahasa Kepri, 2026)
This study aims to examine the influence of Human Resource (HR) Competence, Internal Control, and Information Technology utilization on employee work effectiveness at the Regional Financial and Asset Management Agency (BPKAD) of Batam City. Work effectiveness is a critical factor in supporting accountable, transparent, and service-oriented public governance. The effectiveness of employees’ performance is influenced by several factors, including adequate HR competence, effective internal control systems, and optimal utilization of information technology. This research employed a quantitative approach using a survey method. The study population consisted of all employees of BPKAD Batam City, with a total sample of 89 respondents selected through a census sampling technique. Data were collected using structured questionnaires and analyzed through multiple linear regression using SPSS software. The findings reveal that HR competence has a positive and significant effect on employee work effectiveness. Internal control also demonstrates a positive and significant contribution to improving work effectiveness. Furthermore, information technology utilization has a positive and significant impact and emerges as the most dominant factor influencing employee work effectiveness. Simultaneously, HR competence, internal control, and information technology utilization significantly affect employee work effectiveness, with a coefficient of determination (R²) of 47.2%, indicating that the model explains nearly half of the variation in work effectiveness, while the remaining 52.8% is influenced by other factors beyond the scope of this study. These findings emphasize the importance of strengthening employee competencies, enhancing internal control mechanisms, and accelerating digital transformation initiatives to improve organizational effectiveness. The study contributes to the literature on public sector management by providing empirical evidence that strategic investment in human capital, governance systems, and digital technology can significantly enhance the effectiveness of public service organizations and support the achievement of good governance objectives.